The COVID‐19 pandemic: A community approach. Issue 11 (28th September 2020) - Cravedi, Paolo; Schold, Jesse D.; Safa, Kassem; Kates, Olivia S.; Elfadawy, Nissreen; Mannon, Roslyn B.; Shah, Malay B.; Hammond, Sarah P.; Avery, Robin; Guerrero Miranda, Cesar; Riella, Leonardo V.; Jowsey‐Gregoire, Sheila; et al.
Abstract: An unprecedented global pandemic caused by a novel coronavirus, Severe Acute Respiratory Syndrome Coronavirus 2 (SARS‐CoV‐2) has quickly overwhelmed the health care systems worldwide. While there is an absence of consensus among the community in how to manage solid organ transplant recipients and donors, a platform provided by the American Society of Transplantation online community "Outstanding Questions in Transplantation, " hosted a collaborative multicenter, multinational discussions to share knowledge in a rapidly evolving global situation. Here, we present a summary of the discussion in addition to the latest published literature.